Silk Reservoirs for Local Delivery of Cisplatin for Neuroblastoma Treatment: In Vitro and In Vivo Evaluations - Yavuz, Burcin; Zeki, Jasmine; Taylor, Jordan; Harrington, Kristin; Coburn, Jeannine M.; Ikegaki, Naohiko; Kaplan, David L.; Chiu, Bill (Journal of pharmaceutical sciences, 2019)
Neuroblastoma is the most common extracranial childhood tumor, and current treatment requires surgical resection and multidrug chemotherapy. Local, perioperative delivery of chemotherapeutics is a promising treatment method for solid tumors that require surgical removal. In this study, we have aimed to develop a controlled-release implant system to deliver cisplatin in tumor or tumor resection area. Silk fibroin, a biodegradable, nonimmunogenic biopolymer was used to encapsulate different doses of cisplatin in a reservoir system. The physical integrity of the reservoirs was characterized by evaluating the crystalline structure of silk secondary structure using FTIR spectroscopy. The in vitro release of cisplatin was evaluated in phosphate-buffered saline at 37°C, and the reservoirs were able to release the drug up to 30 days. The cytotoxicity of cisplatin and cisplatin reservoirs were tested on KELLY cells. Cytotoxicity data showed 3.2 μg/mL cisplatin was required to kill 50% of the cell population, and the released cisplatin from the silk reservoirs showed significant cytotoxicity up to 21 days. Intratumoral implantation of silk reservoirs into an orthotopic neuroblastoma mouse model decreased tumor growth significantly when compared with control subjects. These results suggest that silk reservoirs are promising carriers for cisplatin delivery to the tumor site.